2013
DOI: 10.3136/fstr.19.1003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Triterpenoid Isolated from Schizandra chinensis against Acute Alcohol-Induced Liver Injury in Mice

Abstract: Schizandra chinensis (Turcz.) Baill (SC) is useful for the regulation of various pathological conditions in Northeast Asia and is known to possess antioxidant activity. Here, triterpenoid of SC (TSC) was isolated from ethanol-water extracts of SC by using an octadecylsilyl column and shown to be one of the major active constituents of SC. The hepatoprotective effects of TSC in a mouse model of acute alcohol-induced liver injury (AALI) were evaluated based on serum biochemical indicators and antioxidative capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
3
2
0
Order By: Relevance
“…It is well observed that natural antioxidants are able to prevent oxidative stress by donating electrons to scavenge free radicals. Similar results were presented in previous studies in support of the results of reduced MDA levels by antioxidant compounds in alcoholic liver injury models [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is well observed that natural antioxidants are able to prevent oxidative stress by donating electrons to scavenge free radicals. Similar results were presented in previous studies in support of the results of reduced MDA levels by antioxidant compounds in alcoholic liver injury models [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…The ethanol-induced liver injury model group expressed high state of oxidative stress where the levels of GSH and activities of antioxidant enzymes (SOD, GPx, and CAT) were depleted. Similarly, previous studies by Zhang et al [ 19 ] and Zhu et al [ 20 ] also reported the revival of antioxidant defence upon antioxidant administration. Lipid peroxidation has been reported to be the most dangerous reaction in ethanol-induced liver damage [ 8 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The most active fractions, the n-butanol fraction and residual aqueous fraction, which are also the richest in flavonoids, 24 showed anti-hepatoxic activities against DEN, which could be essentially due to known phenolic compounds for their hepatoprotective properties, 21 but also to the steroid and triterpene compounds present in these extracts, 12 and which are also known for their liver-protective capacities. 25 These results are confirmed by the histopathological study, which also shows an improved tissue architecture in sections of livers pretreated with the different fractions. The livers pretreated with the n-butanol and residual aqueous fraction showed improved liver tissue aspects.…”
Section: Hepatoprotective Activitysupporting
confidence: 59%
“…SF prevented the liver injury and hepatic steatosis induced by 5 weeks of ethanol administration [ 17 ]. And the identified active constituents such as lignans, triterpenoids, polysaccharides of SF have been shown to exert the anti-oxidative stress, anti-steatosis, and anti-inflammatory effects against ethanol-induced liver injury [ 10 , 18 , 19 , 20 ]. As for HSCF, the hepatoprotective effect against ethanol consumption has been reported by reducing oxidative stress and fatty changes of liver as well as enhancing endogenous antioxidant activity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%